Scintigraphy of the Parathyroid Glands with 201TI: Experience with 250 Operated Patients - Borsato, N.; Zanco, P.; Camerani, M.; Saitta, B.; Ferlin, G. (Nuklearmedizin - NuclearMedicine, 1989)
Parathyroid scintigraphy confirmed its validity in the preoperative localization of enlarged parathyroids, showing a sensitivity of 82% in a series of 250 patients suffering from primary hyperparathyroidism and successfully operated on. The glands better visualized were in an ectopic site or they were completely or partially outside the thyroid so that they were easily visible without employing digital image subtraction. This is nevertheless necessary to visualize parathyroids in a retrothyroid site but some problems arise, related not only to movements of the patient but also to the instrumentation to perform a correct image subtraction.Die Nebenschilddriisenszintigraphie bestätigte ihre Wertigkeit in der präoperativen Lokalisationsdiagnostik vergrößerter Nebenschilddrüsen. Bei einer Serie von 250 Patienten mit primären Hyperparathyreoidismus und erfolgreicher Operation ergab sich eine Sensitivität von 82%. Jene Nebenschilddrüsen ließen sich besser darstellen, die ektopisch lokalisiert oder die völlig oder teilweise außerhalb der Schilddrüsengrenzen gelegen waren. Diese Nebenschilddrüsen wurden auch ohne digitale Bildsubtraktion leicht sichtbar. Darüber hinaus ist es aber notwendig, auch hinter der Schilddrüse gelegene Nebenschilddrüsen darzustellen. Dabei entstehen allerdings Probleme, die nicht nur durch die Bewegungen des Patienten, sondern auch durch die meßtechnischen Gegebenheiten bei der Bildsubtraktion verursacht werden.